(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aimed to uncover the causes of poor academic achievement of students in public schools in the Qatraneh district in the Karak governorate, and the study sample consisted of (408) male and female students, and the study tool included (43) clauses distributed into three areas (student’sproblems, parent’s problems, and school-specific problems).The results of the study showed that the general level of students ’problems, according to the estimates of the study sample, came at a high or medium level, and that the general level of parents’ problems came at a high level also for most of the clauses, also, the general level of school-specific problems came at an average level, and the results showed that there are statistically significant differences for reasons of weakness and low academic and academic achievement among public school students in the Qatraneh district in the Karak governorate for all fields of study according to the gender variable.The study recommended the necessity of working to address the causes of poor academic achievement according to the fields of study.